Effects of physicochemical parameters on the production of phenolic acids from palm oil mill effluent under liquid-state fermentation by Aspergillus niger IBS-103ZA - Jamal, Parveen; Idris, Zulkarnain Mohamed; Alam, Md. Zahangir (Elsevier, 2011)
The present investigation is an effort to develop an environmentally friendly and cost-effective liquid-state fermentation process by introducing a new locally isolated fungal strain of Aspergillus niger (IBS-103ZA) for the production of phenolics from a new source, palm oil mill effluent (POME). Sucrose, manganese sulphate (MnSO4) and temperature were identified as the most significant variables in improving phenolics production. Optimisation increased the total phenolic content from 856 ± 2.22 to 941 ± 3.72 GAE mg/l at 35.0 °C, 6.0% (w/v) sucrose, 2.7% (w/v) MnSO4, and with other parameters fixed. The fermented extract (FE) with IC50 value of 0.45 mg/ml showed the strongest antioxidant potency, compared to unfermented extract (UFE), with IC50 of 1.13 mg/ml, and the synthetic antioxidant, BHT, with IC50 of 0.63 mg/ml. The phenolic compounds were identified and quantified by HPLC.